2021
DOI: 10.21037/tp-21-244
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol inhibits infantile hemangioma by regulating the miR-424/vascular endothelial growth factor-A (VEGFA) axis

Abstract: Background: Infantile hemangioma (IHA) is the most common tumor in infancy. We aimed to explore the effect of propranolol on the expression of microRNA (miR)-424 in IHA tissues and XPTS-1 cells, as well as its molecular mechanism of inhibiting XPTS-1 cell activity.Methods: Tumor tissues and peritumoral tissue were collected from 13 IHA patients in Lishui Municipal Central Hospital. The level of miR-424 were detected using real-time quantitative reverse transcription polymerase chain reaction (RT-PCR). Cell cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the early laboratory work with Tanshinone extracts, we discovered that eight Tanshinone monomers could significantly inhibit the proliferation of hemangiomas. Cytological and animal experiments showed that the potency of dihydrotanshinone I (DHTS) was 20 times that of propranolol, and that it differs from the possible mechanism of propranolol ( 20 ). We discovered for the first time that a series of Tanshinone compounds isolated from the fat-soluble extract of Tanshin (Tanshinone extract) have a significant inhibitory impact on the proliferation of hemangioma cells (positive control: propranolol).…”
Section: Discussionmentioning
confidence: 99%
“…In the early laboratory work with Tanshinone extracts, we discovered that eight Tanshinone monomers could significantly inhibit the proliferation of hemangiomas. Cytological and animal experiments showed that the potency of dihydrotanshinone I (DHTS) was 20 times that of propranolol, and that it differs from the possible mechanism of propranolol ( 20 ). We discovered for the first time that a series of Tanshinone compounds isolated from the fat-soluble extract of Tanshin (Tanshinone extract) have a significant inhibitory impact on the proliferation of hemangioma cells (positive control: propranolol).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism may be related to the inhibition on the migration of hemangioma endothelial cells, network formation, VEGF-A production, activation of vascular endothelial growth factor receptor 2, and downregulation of the PI3K/Akt and mitogen-activated protein kinase signals. [8][9][10][11] However, regarding whether changes in cytokines in the body affect children's growth and development, there are currently literature reports on monitoring the physical development results of children taking medication, such as height and weight. Tang et al [12] found that oral propranolol treatment for infantile hemangioma children had a certain impact on physical development indices in a study of 116 such children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that propranolol inhibits the angiogenesis of normal endothelial cells, as well as the angiogenesis of hemangioma ( Chim et al, 2012 ; Lamy et al, 2010 ). It has also been shown that propranolol inhibits the proliferation and induces the apoptosis of endothelial cells within hemangioma, which was mediated by the suppression of vascular endothelial growth factor A (VEGFA) expression ( Tavakoli et al, 2017 ; Wu et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%